Induced pluripotent stem cells in periodontal reconstructive therapy: A narrative review of pre-clinical studies - Hendrawan, Reza Dony; Prahasanti, Chiquita; Savitri, Irma Josefina; Hari, Padmini (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Regenerative periodontal surgical therapy faces significant challenges due to the limited ability of the body to regenerate damaged periodontal tissue. One of the primary goals in regenerative periodontal therapy is regaining periodontal tissue attachment after destruction by periodontal disease. Currently, stem cells, harnessing three pivotal components”cells, biomaterials, and growth factors”are widely used in periodontal regeneration. Stem cells can be obtained from various sources, either by isolating cells from bone marrow, teeth, and muscles or through the somatic cell programming method (reprogramming) known as induced pluripotent stem cells (iPSCs). Purpose: This review aims to describe the potential use of iPSCs in the treatment of periodontal defects. Review: Search strategies were developed using the PubMed, LILACS, Scielo, and Wiley online databases during the period of 2012–2022. Ten articles met the inclusion criteria. iPSCs were obtained by inducing somatic cells from both dental and non-dental sources with factors Oct3/4, Sox2, Klf4, and c-Myc. Periodontal tissue regeneration procedures can be augmented with iPSCs. Unlike tooth-based stem cells, iPSCs offer several advantages, such as unlimited cell sources and the capability to differentiate into any cell type, including periodontal tissue. The potential of iPSCs extends to correcting periodontal bone defects and forming new periodontal tissues, such as alveolar bone, cementum, and periodontal ligament. However, iPSCs do have limitations, including the need for clinical trials, cell programming production facilities, and optimization of differentiated-cell functionality. Conclusion: The combined use of iPSCs in cell-based tissue engineering holds vast potential for future periodontal treatment strategies.